2019
DOI: 10.1007/s40204-019-00121-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel polycaprolactone/carbon nanofiber composite as a conductive neural guidance channel: an in vitro and in vivo study

Abstract: The current study aimed to investigate the potential of carbon nanofibers to promote peripheral nerve regeneration. The carbon nanofiber-imbedded scaffolds were produced from polycaprolactone and carbon nanofibers using thermally induced phase separation method. Electrospinning technique was utilized to fabricate polycaprolactone/collagen nanofibrous sheets. The incorporation of carbon nanofibers into polycaprolactone's matrix significantly reduced its electrical resistance from 4.3 × 10 9 ± 0.34 × 10 9 Ω to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…A polycaprolactone/carbon nanofiber sheets composite was first tested in vitro and then in vivo. Farzamfar and colleagues found that such nanofiber sheets implanted in rat sciatic nerve promoted cell attachment, proliferation, and neurite out-growth [134]. Another useful functionalization of polycaprolactone has been obtained with laminin.…”
Section: Nanofibersmentioning
confidence: 99%
“…A polycaprolactone/carbon nanofiber sheets composite was first tested in vitro and then in vivo. Farzamfar and colleagues found that such nanofiber sheets implanted in rat sciatic nerve promoted cell attachment, proliferation, and neurite out-growth [134]. Another useful functionalization of polycaprolactone has been obtained with laminin.…”
Section: Nanofibersmentioning
confidence: 99%
“…27 A similar study was performed by Farzamfar et al, which supported the successful nerve regeneration in a critical-sized sciatic nerve defect in a rat model. 28 Prior studies reported the higher healing potential of CNF conductive scaffolds compared with nonconductive scaffolds. 25,[29][30][31] CNF are engineered as cylindrical nanostructures with a high aspect ratio, and excellent thermal conductivity, mechanical, and electrical properties, making them ideal for biological applications since cells require a threedimensional matrix environment for efficient growth.…”
Section: Introductionmentioning
confidence: 98%
“…Alginate/chitosan conduits induce more extensive axon regeneration when they contain or release simvastatin [183], NGF [184][185][186][187], GDNF [184], VEGF [188], GDNF and NGF [24,189], or pleiotrophin [15]. Efficacy is also increased when alginate/chitosan conduits are combined with fibronectin, laminin [190], or when hydrogel conduits contain Matrigel, collagen, heparin (sulfate), laminin, or fibronectin [190]. Conduit efficacy is further increased by the release of neurotrophic factors within conduits from biodegradable polymeric with aligned heparin-conjugated nanofibers [191,192].…”
Section: Conduits Containing Neurotrophic and Other Factorsmentioning
confidence: 99%
“…The efficacy of fibrin conduits is enhanced when they are filled with autologous undifferentiated adipose-derived stem cells [145] or contain mesenchymal stem cells [195], and when hydrogel conduits contain mesenchymal stem cells [196]. The efficacy of chitosan conduits is enhanced when they contain combinations of fibronectin and laminin with mesenchymal stem cells (MSCs) or Schwann cells [190], chitosan/PLGA scaffolds are combined with mesenchymal stem cells [197], and when three-dimensional alginate/chitosan conduits are filled with muscle fibers [198]. Adding PRP to the inside of silicon tubes bridging nerve gaps increases the extent of axon regeneration compared to that induced by empty silicon conduits [149,198,199].…”
Section: Conduits Containing Cellsmentioning
confidence: 99%